Prevalence of dry eye amongst computer workers in Kanpur - Mallik, Debayan; Gahlot, Anju; Maini, Ashok; Garg, Sughandha (International Journal Of Community Medicine And Public Health, 2017)
Background: The increased use of computers in the workplace has brought about the development of a number of health concerns majority related to eyes which prompted us to carry out this study to find out the factors relating to eye and vision problems associated with computer work and recommendations for preventing or reducing their developments. Methods: This was a cross-sectional study, which was carried out amongst employees of Rama University, Mandhana, Kanpur, India. The data was collected between June 2016 and October 2016. A total of 214 individuals gave their consent and participated in the study. A pretested, semi-structured questionnaire was used to collect the data. Results: 214 personnel were interviewed. Mean age of study subjects was 33.5±11.013 years with 58.88% of subjects being in the age group of 25-35 years. 49 (22.9%) reported spending 2-3 hours 118 (54.83%) spent 3-6 hour/day, while 47 (22%) of the respondents spent more than 6 hour/day working on a computer. Prevalence of dry eye was found to be 75% (160/214). The common symptoms were watery eyes (31.77%), followed by sensitivity to light & blurring of vision (both 17.76%), sensation of having something in the eyes (14.95%), difficulty in night time driving (13.08%), eye redness (11.21%) and difficulty in wearing contact lenses (5.6%). Conclusions:Three fourth of the computer professionals we studied had mentioned to have some computer-related health problems. This is a significant proportion and denotes that the occupational health of the people working in the computer field should be emphasized as a field of concern in public health. The ergonomics of the working environment of the computer professionals have a direct impact on their wellbeing. Hence the organizations employing them, as well as the professionals themselves need to be sensitized regarding the importance of the regular eye & health check-ups and proper working conditions.